Virtual technologies and e-collaboration for the future of global business - Richards, Joseph; Zhao, Jingyuan (IGI Global, 2022)
"The book focuses on emerging technologies and tools for collaboration in virtual environments, and includes the most new findings in in Automation, Computing and Intelligent Information Systems, as well as state-of-the-art solutions covering various issues and challenges
Includes bibliographical references and index. - Mode of access: World Wide Web
Keywords: Business enterprises -- Computer networks; Business networks; Communication -- Technological innovations